PHYTOCHEMICAL TEST and BRINE SHRIMP LETHALITY TEST AGAINST Artemia salina LEACH OF ANTING-ANTING (Acalypha indica Linn.) PLANT EXTRACT - Hayati, Elok Kamilah (Jurusan Kimia, Fakultas Sains dan Teknologi UIN Maulana Malik Ibrahim Malang, 2012)
Phytochemical test and brine shrimp lethality test against Artemia salina Leach of anting-anting (Acalypha indica Linn.) plant extract had been conducted. Al Quran surah Asy Syu’ara verse 7 shows advantages of plant, such as to medicine. The aim of this research is to measure the toxicity level of each anting-anting extract with three different solvents using Artemia salina Leach and to find out the compound in extracts which has a bioactivity potency. Three solvents which used in maceration process to produce anting-anting extracts are ethanol, chloroform and n-hexane. Anting-anting plant was macerated for 24 hours and shacked for 5 hours. Each of solvent extract were examined with Brine Shrimp Lethality Test and its compound with reagent and supported by thin layer chromatography. The mortality of Artemia salina analyzed by probit analyst. The Lethal Concentration 50 (LC50) values of n-hexane, ethanol and chloroform extracts, respectively are 57,0933 ppm, 73,4575 ppm and 149,374 ppm. All three LC50 values are less than 1000 ppm, from those numbers can be concluded that anting-anting extract has a bioactivity potency. The phytochemical compounds in each solvent extract are flavonoid (ethanol extract), steroid (chloroform extract) and triterpenoid (ethanol and n-hexane extract). Key Words: Anting-anting (Acalypha indica Linn.), Artemia salina Leach, phytochemical test, toxicity test